Disaster Preparedness for Children: Systematic Literature Review Study - Ramdani Salam; Eva Marthinu; Rahim Achmad; Putri Adibatur Rohmah; Wiwik Lestari (Jurnal Penelitian Pendidikan Geografi, 2025)
Ternate City, situated on the Pacific Ring of Fire, faces frequent natural disasters, particularly volcanic eruptions from Mount Gamalama, posing significant risks to children. This study aims to address the gap in disaster education by evaluating existing programs and providing actionable recommendations to enhance children's preparedness. A systematic literature review analyzed data from databases like Scopus and Google Scholar, focusing on disaster education tailored to children in volcanic regions. The findings highlight the benefits of disaster education programs in improving children's knowledge, awareness, and resilience. Effective programs emphasize age-appropriate learning methods, community engagement, and psychological preparedness. However, gaps remain in implementation, especially concerning innovative teaching tools and comprehensive risk education. This study recommends incorporating localized cultural contexts, creative teaching methods, and the integration of disaster education into school curricula. These measures aim to empower children as active participants in disaster risk reduction, fostering a more resilient community.